The expert vascular access nurse: a pilot study of competencies - Sollami, Alfonso; Fabbri, Elisa; Bertolaccini, Luca (Acta Biomedica Atenei Parmensis, 2023)
Background and aim In health care, competencies evolving with clinical and professional practice increasingly need to be defined. Identifying professional competencies in a general sense is no longer enough; it is necessary to define what competencies the professional must possess to ensure the appropriateness and effectiveness of their work. This pilot study aims to outline an initial competency framework specifically for vascular access nurses Methods: A cross-sectional observational study was conducted through structured interviews with professionals of a competency framework (108) to assess content validity and ensure relevance, comprehensibility, and completeness Results: The research involved 14 expert professionals who reported no significant language barriers or comprehensibility difficulties. The expert review showed that the content was valid for all proposed items (CVR .571 to 1.0). Conclusions: The framework identified could be a good starting point for a more in-depth assessment of expert nursing skills in venous access (www.actabiomedica.it)